Hodnocení výkonnosti společnosti s využitím EFQM Excelence Model - Kocián, Oldřich (Vysoké učení technické v Brně. Fakulta podnikatelská, 2021)
Diplomová práce hodnotí výkonnost společnosti SUEZ CZ a.s. prostřednictvím EFQM Excelence Model a následně pojednává o návrzích na zlepšení dosavadní výkonnosti společnosti. Práce je rozdělena do tří částí. První část obsahuje nezbytná teoretická východiska, druhá část práce tyto východiska využívá a aplikuje na vybranou společnost SUEZ CZ a.s. Třetí část vyhodnocuje provedené dotazníkové šetření a navrhuje opatření ke zlepšení v problémových oblastech.

The master’s thesis evaluates the performance of SUEZ CZ a.s. company applying the EFQM Excellence Model and subsequently discusses proposals to improve company’s performance. The thesis is divided into three parts. The first part outlines the necessary theoretical bases, that are further used and applied to the chosen company SUEZ CZ a.s. in the second part. Lastly, in the third part, the conducted questionnaire survey is evaluated and measures for improvement in problematic areas are proposed.
The Performance Evaluation of the Company using the EFQM Excellence Model
Keywords: výkonnost společnosti; EFQM Excelence Model; Model START; hodnocení; výsledky; předpoklady; company performance; EFQM Excellence Model; Model START; evaluation; results; enablers